Building Human Capital : Lessons from Country Experiences – Ghana - Blunch, Niels-Hugo (World Bank, Washington, DC, 2020)
Ghana has made deliberate efforts to invest in health and education in the last 60 years, which has resulted in substantial gains in both economic growth and human capital outcomes. This case study examines the recent human capital developments in Ghana in the context of the World Bank’s Human Capital Index, launched in 2018. First, it identifies the two components that have been key drivers of the Ghana’s improving HCI scores in recent years, namely childhood stunting and enrollment rates. The study then goes on to identify the specific policies and programs in Ghana that are probable contributors to the favorable developments in childhood stunting and enrollment rates with the aim of enabling policymakers in other countries to learn from what worked and what did not work in Ghana as they embark on their own national journeys to build human capital. In so doing, the paper deliberately focuses on multisectoral initiatives. The report finds that some of Ghana’s most successful programs and policies have included strong elements of a whole of government approach, involving not just either the health or education sectors but frequently both, as well as other sectors, such as agriculture and WASH (water, sanitation, and hygiene). These successful programs and policies include the Ghana School Feeding Program (GSFP); the National Health Insurance Scheme (NHIS) (especially in the beginning as sustainability has increasingly become an issue in later years); water and sanitation, and hygiene (WASH) activities; Free Compulsory Universal Basic Education (FCUBE), including the innovative financing provided by the Ghana Education Trust Fund (GETFund), and adult literacy programs.